Examination of Students' Small Groups Discussion in Argumentation Process: Scientific and Socio-Scientific Issues - Esra Kabatas-Memis; Ebru Ezberci Cevik (Seyit Ahmet Kıray, 2017)
The purpose of this study was to examine processes experienced by students of different achievement levels in small group discussions in argumentation applications conducted in scientific and socio-scientific issues. Case study which is a qualitative research design was used for the study. In this line, a success test including mechanical subjects comprising multiple-choice and open-ended questions was applied to students by researches in the beginning of semester. Looking at points taken from the success test, student levels (high, medium and low) were determined and groups were formed in accordance with these levels. One group was selected from each level representing that level, and processes experienced by discussions relating to scientific issue as well as socio-scientific issue were individually examined. Study group consisted of 10 preservice teachers having education in Department of Science Teaching. Voice records of both issues were taken during student discussions and analyzed by transcription. Codes prepared by the researchers (cause-effect relationship, using clues, proposing suggestions, prediction, deduction etc.) were combined under certain categories and entitled. As a consequence, it was revealed that students were more effective in supporting argumentation process in non-scientific issue with respect to scientific issue; and in terms of evaluation, metacognition and process management, students were more effective in scientific issue with respect to non-scientific issue. Moreover, it was seen that students were more effective in non-scientific issue with respect to scientific issue in scientific process skills. When student-student questions were examined, there were more questions in scientific issue in the low-level; and there were more questions in non-scientific issue in the medium level.